The effect of proposed educational activities in Science curriculum the development of Preventive education dimensions among intermediate stage female students - Al-Harbi, Noura Abdulaziz (Journal of Educational and Psychological Sciences, 2020)
This study aimed at identifying the effect of using proposed educational activities in Science curriculum the development of Preventive education dimensions among intermediate stage female students, the researchers prepared a teacher’s guide and Preventive education dimensions scale that contained 30 items. Validity and stability of the tools and materials were verified. The researcher used the quasi-experimental approach and applied the tools on the study sample that consists of 48 students, among the students of the second average class in the city of Mecca, the results of this study have shown statistically significant differences at the level of α ≥ 0,05 between the mean scores of the control group and the experimental in and awareness scale in favor of the experimental group, it also resulted in impact values ​​d = 5.6, which is a value that indicates the large impact that occurred on the experimental group in raising awareness of the dimensions of preventive education, and accordingly recommendations and some proposals were presented, the most important of which is the need to include educational educational activities in the curricula of teacher preparation programs; It has effectiveness in the teaching and learning process, conducting a semi-experimental study on the effectiveness of applying a proposed unit on health and nutritional awareness to middle school students in developing awareness of the dimensions of preventive education.